Application of Cooperative Learning Model of Two Stay-Two Stray (TSTS) Type on the Reaction Rate Material on the Students’ Learning Outcomes in Class XI SMA Negeri 1 Banawa Tengah - Alfiani Alfiani; Irwan Said; Vanny M. A. Tiwow (Jurnal Akademika Kimia, 2020)
This study aims to analyze the influence of students’ learning outcomes on reaction rate by applying the cooperative learning model type TSTS (two stay-two stray) in class XI SMA Negeri 1 Banawa Tengah. The type of research was quasi-experimental (quasi-experimental research) with a nonrandomized pretest-posttest control group design. This study was conducted on two classes, namely class XI IPA 1 as an experimental (n= 32) and class XI IPA 2 as the control class (n= 32). Analysis data used the two-party t-test statistical with the prerequisite test, namely normality and homogeneity test. The results showed that the learning outcomes of students in the experimental class X̅1was 76.93 with a standard deviation = 8.62 while in the control class X̅2 was 72.06 with a standard deviation= 8.53. The results of hypothesis testing obtained – ttable≤ tcount + ttable which was -1.67 <3.25> +1.67 with a significant level (α= 0.05) and degrees of freedom = 62. This showed that H0 was rejected and H1was accepted it can be concluded that there is an effect of the application of the two stay-two stray (TSTS) type cooperative learning model on the reaction rate to the students’ learning outcomes of class XI SMA Negeri 1 Banawa Tengah.